Vietnamese Primary School Teachers’ Needs for Professional Development in Response to Curriculum Reform - Yen Thi Xuan Nguyen (Education Research International, 2022)
This qualitative study explored the needs for teacher professional development (PD) of Vietnamese primary school teachers. The participants of the study were ten teachers at ten different primary schools in a large city in Vietnam. The data included in-depth individual interviews with the participating teachers. Qualitative analysis of the interview transcripts revealed several interesting insights into the teachers’ perspectives on PD, their regular PD activities, and their needs for PD. All the teachers considered PD essential for their demanding teaching job. They reported having attended various PD programs and activities provided by their schools, and the department of education and training at the province and district levels. They also participated in several teacher professional learning communities available on the Internet. However, the teachers expressed a need for more PD programs and activities, especially in the context of curriculum reforms. Notably, they preferred to attend PD courses which were more practical and relevant to their work. In addition, they highly appreciated the hands-on activities and opportunities to interact with teacher trainers and educators. These findings were interpreted and discussed in relation to the sociocultural contexts of Vietnamese primary education. The study also discussed implications for PD course designers and teacher educators in Vietnamese primary school contexts and beyond.